2004
DOI: 10.1182/blood-2004-04-1277
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulant treatment: friend or foe in cardiovascular disease?

Abstract: Calcification is a common complication in cardiovascular disease and may affect both arteries and heart valves. Matrix ␥-carboxyglutamic acid (Gla) protein (MGP) is a potent inhibitor of vascular calcification, the activity of which is regulated by vitamin K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 12 publications
6
119
0
6
Order By: Relevance
“…Vitamin K antagonists such as warfarin induce the incomplete g-carboxylation of matrix g-carboxyglutamic acid protein and attenuate the synthesis and function of matrix g-carboxyglutamic acid protein. 24 Previous observational studies in Western countries showed that aortic valve calcifications were significantly larger in patients treated with oral anticoagulants, 25,26 a finding that is compatible with our current data from Japanese patients. In a society with many elderly, such as in Western countries and Japan, the use of oral anticoagulants to prevent thromboembolic events has increased correspondingly with the rising prevalence of atrial fibrillation, but the effects of warfarin on the progression of CAVD were independent of the presence of atrial fibrillation in this study.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdsupporting
confidence: 82%
“…Vitamin K antagonists such as warfarin induce the incomplete g-carboxylation of matrix g-carboxyglutamic acid protein and attenuate the synthesis and function of matrix g-carboxyglutamic acid protein. 24 Previous observational studies in Western countries showed that aortic valve calcifications were significantly larger in patients treated with oral anticoagulants, 25,26 a finding that is compatible with our current data from Japanese patients. In a society with many elderly, such as in Western countries and Japan, the use of oral anticoagulants to prevent thromboembolic events has increased correspondingly with the rising prevalence of atrial fibrillation, but the effects of warfarin on the progression of CAVD were independent of the presence of atrial fibrillation in this study.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdsupporting
confidence: 82%
“…However, a small computed tomography study found that warfarin use was associated with both valvular and coronary calcification (41). Histopathologic examination of aortic valves replaced for aortic stenosis found that those patients treated with warfarin had a two-fold increase in valvular calcification (42). Warfarin initiation has also been associated with calcemic uremic arteriopathy (43), a systemic vascular calcification syndrome typically involving small capillaries.…”
Section: Warfarin's Effect On the Vasculaturementioning
confidence: 99%
“…The vitamin K antagonist war-farin may block vitamin K-dependent c-carboxylation within the liver and prevent hepatic formation of clotting factors. However, this process is not limited to the liver, and carboxylation of peripherally expressed vitamin K-dependent protein may be affected as well, thereby regulating calcium binding [8][9][10]. Thus, although the relationship between warfarin and vascular calcification in humans is not fully understood, observational studies suggest that inhibition of MGP carboxylation by the vitamin K antagonist warfarin results in extensive calcification of arteries in vitro and in vivo because of synthesis of the inactive undercarboxylated MGP (ucMGP) [10,11].…”
Section: Introductionmentioning
confidence: 99%